2003
DOI: 10.1128/iai.71.4.1763-1773.2003
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Control and Antigen-Specific T Cells on Intracellular Mycobacterial Growth

Abstract: It is estimated that one-third of the world's population is infected with Mycobacterium tuberculosis and that tuberculosis (TB) kills more than 2 million people each year (4). Intradermal vaccination of infants with the currently available TB vaccine Mycobacterium bovis bacillus Calmette-Guérin (BCG) can induce partial protection against TB disease (7) but does not prevent initial or latent infection with M. tuberculosis. Once infected, individuals are at chronic risk for TB disease progression and secondary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 52 publications
2
71
0
Order By: Relevance
“…The experimental design for the experiment was similar to that of work previously described (15,49). For each condition, 4 ϫ 10 4 DCs were resuspended in a total volume of 200 l RPMI medium, RPMI medium plus recombinant human IL-10 (BD Biosciences), control hepatocyte culture medium, or supernatants from HCV-infected hepatocytes.…”
Section: Cells and Transfectionsmentioning
confidence: 99%
“…The experimental design for the experiment was similar to that of work previously described (15,49). For each condition, 4 ϫ 10 4 DCs were resuspended in a total volume of 200 l RPMI medium, RPMI medium plus recombinant human IL-10 (BD Biosciences), control hepatocyte culture medium, or supernatants from HCV-infected hepatocytes.…”
Section: Cells and Transfectionsmentioning
confidence: 99%
“…Perforin appears to be required for granulysin to enter infected cells and lyse intracellular organisms (1). Despite the cytoplasmic association in granules and cooperative mechanism of action, the levels of protein expressed in infected tissue and mRNA detected after Ag-specific recall indicate that granulysin expression may be regulated separately from perforin upon T cell activation (16,17). Currently, one of the most interesting antimicrobial activities associated with granulysin is the ability to directly kill mycobacteria (18).…”
mentioning
confidence: 99%
“…Mycobacterium tuberculosis can be lysed extracellularly by granulysin or NK-lysin (1,5,7), and lysed intracellularly by granulysin following permeation of the cellular membrane by perforin (1). Granulysin-dependent killing of M. tuberculosis-infected targets by CD4 ϩ , CD8 ϩ , and ␥␦ T cells has been inferred from in vitro studies in which granule-dependent killing occurred despite blocking perforin and/or granzyme activity (1,3,16,21,22). Cytotoxic activity by T lymphocytes against Mycobacterium bovis bacillus Calmette-Guérin (BCG) 3 -infected macrophages correlates to increased expression of granulysin in human T cells isolated from peripheral blood of subjects reactive to purified protein derivative (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Worku and Hoft have previously demonstrated that increased mRNA expression of perforin, granzyme and granulysin contribute to a protective host response in human TB [27]. This improved mechanism of protection has also been demonstrated using antibody blockage of the granule exocytosis pathway, that dramatically reduced the lytic activity of T cells against Mtb-infected macrophages and the increase of intracellular growth of bacteria [28].…”
Section: Discussionmentioning
confidence: 91%